Functional outcome and quality of life of patient with post traumatic osteomyelitis of the femur and tibia - Mohd Yusof, Nazri; Sulong, Ahmad Fadzli (2016)
This study was conducted to evaluate the clinical outcome, functional outcome, and quality of life of patients treated for post traumatic osteomyelitis (PTO) of femur or tibia in Hospital Tengku Ampuan Afzan, Kuantan, Malaysia. A total of 119 patients were identified from the operating records from June 2007 until June 2014. 47 patients consented and participated in this study. The median age of participants was 44 years old, and ranges from 16 to 80 years old. There were 26 tibia and 21 femur osteomyelitis evaluated in this study. 38 participants (80.9%) had implants inserted and 9 participants (19.1%) had no implants. The participants were follow up for a mean duration of 4.4 years (range 1.7-9.5 years). Interviews were then conducted and clinical assessments were performed to evaluate the clinical outcome. Their functional outcomes were evaluated using the Lower Extremity Functional Score (LEFS) and the quality of life were evaluated using the SF-36v2 (validated and translated into Malay Language). As for the results, 93.6% of participants had a successful treatment and achieved union without recurrence of infection. 3 (6.4%) participants had failure of treatment were from CM-IIIA, CM-IVA, and CM-IVB. Staphylococcus aureus and MRSA were the 2 commonest microorganisms isolated from the culture. The mean scores of SF-36v2 of participants with PTO were significantly lower compared to the Malaysian general population. However with increasing age, the general health and vitality were similar with the Malaysian general population. Concurrent medical problem and CMB (Systemic) hosts significantly contributed to poorer functional outcome, and lower quality of life score especially the Physical Component domain. In conclusion, most patients with post traumatic osteomyelitis had successful treatment. However their quality of life were poorer in comparison to the Malaysian general population. Concurrent medical problem and CM-B(Systemic) hosts had significantly poorer functional outcome and quality of life than healthy patients.